Synthesis, spectral investigation and antimicrobial assay of 2-ethoxy-6-(((3-nitrophenyl)imino)methyl)phenol and its Co(II) and Cu(II) complexes - V. Gomathi; Rajendran Rajaram; K. Kayathri Devi; M. Gayathri; P. Ishwarya; P. Jagatheeshwari; R. Karthika; D. Keerthana (Discover Chemistry)
Abstract In the present work, [Co2(EN-H)2Cl2] and [Cu2(EN-H)2Cl2] were synthesized using Schiff base, 2-ethoxy-6-(((3-nitrophenyl)imino)methyl)phenol [EN(3)], which is derived from 3-nitroaniline and 3-ethoxysalicylaldehyde. The nature of bonding and the structural features of the Schiff base and its complexes have been deduced using molar conductance, Fourier Transfrom Infra-Red (FT-IR), electronic, 1H NMR, mass, and fluorescence spectra. The antimicrobial activities of Schiff base, and its Co(II) and Cu(II) complexes were investigated against Staphylococcus aureus, Escherichia coli, and Aspergillus niger by agar-well diffusion method. Both the Schiff base and complexes exhibit substantial activities. The [Cu2(EN-H)2Cl2] displays significant antimicrobial activity compared to the standard drug oxytetracycline and amphotericin B, which suggests the potential antimicrobial activity. The efficiency order towards Staphylococcus aureus is EN(3) < [Co2(EN-H)2Cl2] < standard drug < [Cu2(EN-H)2Cl2]. In case of E. coli, the order is EN(3) < standard drug < [Co2(EN-H)2Cl2] < [Cu2(EN-H)2Cl2].The efficacy order against Aspergillus niger is standard drug < EN(3) < [Co2(EN-H)2Cl2] < [Cu2(EN-H)2Cl2]. From the obtained results, it is arrived that the proposed complexes possess antimicrobial, as well as antifungal activities.